2016
DOI: 10.1016/j.dib.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Morbility, clinical data and proteomic analysis of IUGR and AGA newborns at different gestational ages

Abstract: The data are related to the proteomic analysis of 43 newborns with intrauterine growth retardation (IUGR) and 45 newborns with appropriate weight for gestational age (AGA) carried out by separation via 2DE and analyzed by MS–TOF/TOF. All newborns were separated into three gestational age groups, "Very Preterm" 29–32 weeks, "Moderate Preterm" 33–36 weeks, and, "Term" ≥37weeks. From each newborn, blood was drawn three times from birth to 1 month life. High-abundant serum proteins were depleted, and the minority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was demonstrated that procalcitonin was not associated with gestational week or birth [30]. Ruiz Gonzalez et al showed that serum CRP and procalcitonin levels were not different between IUGR and AGA neonates [31]. We therefore assessed procalcitonin levels in patients with IUGR and combined this analysis with procalcitonin levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that procalcitonin was not associated with gestational week or birth [30]. Ruiz Gonzalez et al showed that serum CRP and procalcitonin levels were not different between IUGR and AGA neonates [31]. We therefore assessed procalcitonin levels in patients with IUGR and combined this analysis with procalcitonin levels.…”
Section: Discussionmentioning
confidence: 99%